Integration of biological effects, fish histopathology and contaminant measurements for the assessment of fish health: A pilot application in Irish marine waters. (August 2017) - Giltrap, Michelle; Ronan, Jenny; Bignell, John P.; Lyons, Brett P.; Collins, Evelyn; Rochford, Heather; McHugh, Brendan; McGovern, Evin; Bull, Lorraine; Wilson, James
Abstract: This study investigates the use of a weight of evidence (WOE) approach to evaluate fish health status and biological effects (BEs) of contaminants for assessment of ecosystem health and discusses its potential application in support of the Marine Strategy Framework Directive (MSFD). External fish disease, liver histopathology and several BEs of contaminant exposure including 7-ethoxy resorufin O-de-ethylase( EROD), acetylcholinesterase (AChE), bile metabolites, vitellogenin (VTG) and alkali labile phosphates (ALP) were measured in two flatfish species from four locations in Ireland. Contaminant levels in fish were generally low with PCBs in fish liver below OSPAR environmental assessment criteria (EAC). There were consistencies with low PCB levels, EROD and PAH bile metabolite levels detected in fish. Dab from Cork, Dublin and Shannon had the highest relative prevalence of liver lesions associated with the carcinogenic pathway. An integrated biomarker response (IBR) showed promise to be useful for evaluation of environmental risk, although more contaminant parameters in liver are required for a full assessment with the present study. Highlights: An integrated biomarker response was used to assess multiple biomarkers in flatfish. Dab and plaice proved to be valuable monitoring species. Fish histopathology and biomarkers were used in a weigh of evidence approach.